A literatura como instrumento de efetivação da educação em direitos humanos: a aplicação de uma sequência didática envolvendo uma reescritura da obra "Os miseráveis" - Lima, Déborah Justiniano Vieira (2020)
This research aims to enhance the importance of Literature as a way of implementing Human Rights Education by means of the application of a didactic sequence that prioritizes the humanizing function of Literature. This work is justified by the need to educate for life, training students who are aware of the possibilities of knowing and controlling the factors that lead them to their autonomy and valuing Literature both in its aesthetic and social function, promoting a parallel between the fictional text and the reality experienced by the students. The concern with Human Rights Education has grown in Brazil. Consequently, there is a need for the development of projects that arouse respect for differences, tolerance and awareness of the dignity of every human person. Literature, therefore, assumes a fundamental role in terms of raising student awareness of topics related to Human Rights. Given this context, it is necessary to rethink the teaching of Literature, often focused exclusively on formal and classification issues, expanding its relevance for discussions pointed out in the historical and social context of its plots. To this end, it was decided to study, in Portuguese Language classes, the classic Les Misérables, by Victor Hugo, adapted for children and adolescents by Luc Lefort, since the class in issue was a 6th grade of an elementary school in a municipal school of Goiânia, Goiás. In the specific case of this research, the approach started from a critical reading of analysis and discussion with students about the plot of a rewritten work with the purpose of establishing a relationship with Human Rights. As Literature, according to Candido (1988), is considered a human right, why not working through a metalinguistic exercise in which human rights are discussed in the work in question? It is Literature manifesting itself as a human right and debating the meaning of "Human Law" itself. Through the application of the basic sequence proposed by Cosson (2016), prioritizing the humanizing function of Literature and through a social approach, we sought to encourage the student to take a position on social issues, and even intervene in their reality seeking to transform it. The work was positive in the sense that the students were interested in the project and, mainly, in reading the literary book and were able to know and reflect on their rights. In view of the questions here presented, which sought to foster a taste for literary reading among students and to rely on Literature to carry out an education in Human Rights, it is also expected that this study may contribute to assist Portuguese Language teachers interested in working with the rewrites of classics and the humanizing principle of Literature.